2018
DOI: 10.1002/jmri.26014
|View full text |Cite
|
Sign up to set email alerts
|

Segmentation of gray matter, white matter, and CSF with fluid and white matter suppression using MP2RAGE

Abstract: 2 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2018;48:1540-1550.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
(112 reference statements)
0
15
0
Order By: Relevance
“…The proposed method allows rapid processing with relevant segmentation of brain tissues. A recent study has reported MP2RAGE-based segmentation using two images with different inversion times, i.e., INV1 and INV2 [28]. The study demonstrated superior segmentation in subcortical structures in comparison with FSL and SPM12, whereas our proposed method produced good segmentation in the cerebellum and WM in the medial part of the brain.…”
Section: Discussionmentioning
confidence: 74%
“…The proposed method allows rapid processing with relevant segmentation of brain tissues. A recent study has reported MP2RAGE-based segmentation using two images with different inversion times, i.e., INV1 and INV2 [28]. The study demonstrated superior segmentation in subcortical structures in comparison with FSL and SPM12, whereas our proposed method produced good segmentation in the cerebellum and WM in the medial part of the brain.…”
Section: Discussionmentioning
confidence: 74%
“…The proposed method allows rapid processing with relevant segmentation of brain tissues. A recent study has reported MP2RAGE-based segmentation using two images with different inversion times, i.e., INV1 and INV2 [31]. The study demonstrated superior segmentation in subcortical structures in comparison with FSL and SPM12, whereas our proposed method produced good segmentation in the cerebellum and WM in the medial part of the brain.…”
Section: Discussionmentioning
confidence: 81%
“…We would deploy the sequence in the event we observed pathology on one of the conventional anatomical scans. A future protocol might also include MP2RAGE for tissue and CSF segmentation (Wang et al . 2018), for enhanced deep gray matter contrast (Tanner et al .…”
Section: Discussionmentioning
confidence: 99%